Knowledge, attitudes, and practice about protective ventilation among physical therapists - Iara Sayuri Shimizu; Sângia Feucht Freire; Mayson Laercio de Araujo Sousa; Juliana Carvalho Ferreira (PLoS ONE, 2025)
Objectives To measure knowledge, attitudes and practice (KAP) towards protective ventilation and identify factors associated with KAP among physical therapists in a country-wide survey. Methods We conducted an online survey using a validated questionnaire with 55 items including individual and institutional information, KAP, and barriers to protective ventilation. The survey was distributed by email and social media. We calculated a total KAP score and scores for knowledge, attitudes, and practice, using a standardized scale from 0 to 100. Results We included 408 participants from all states of Brazil. Median knowledge score was 80 (IQR 72–88) out of 100, with 95% respondents agreeing that they were familiar with the ventilatory settings to achieve protective ventilation, but 34% reported that airway pressures are not always discussed during rounds. Total KAP score had a median of 71 (62–79) out of 100. In the multivariate analysis, years of ICU experience, attending conferences, and ICU beds per physical therapist were independently associated with KAP score. The most significant barriers to protective ventilation were lack of education to provide low tidal volume ventilation and maintaining protective ventilation in pressure support. Participants reported there was an increase in the practice of protective ventilation during COVID-19 pandemic. Conclusions In this countrywide study, physical therapists had good knowledge, attitudes, and practice regarding protective ventilation, and lack of education was an important factor associated with KAP. Discussing airway pressures during ICU rounds and developing specific training may improve awareness and practice of protective ventilation and impact patient outcomes.